2008
DOI: 10.1007/s10592-008-9699-6
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and characterization of microsatellite loci from a potential biofuel plant Miscanthus sinensis (Poaceae)

Abstract: Miscanthus sinensis (Poaceae) is typical of many dominant grasses of East Asia. Due to its characteristics of fast growth and high biomass, Miscanthus, a C4 plant, has been long explored for the potential usage as biofuel. In this study, we described the development of nine microsatellite loci from M. sinensis for genetic studies. These new markers were tested in 25 individuals of five populations in three varieties. The number of alleles ranged from 3 to 8. The expected (H E ) and observed (H O ) heterozygosi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
29
1

Year Published

2011
2011
2014
2014

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(33 citation statements)
references
References 9 publications
3
29
1
Order By: Relevance
“…It is interesting that despite the ability of M. sinensis to spread in the USA and form wild populations (Quinn , values for heterozygosity for the species overall were still smaller than expected for long-lived perennial species, outcrossing species, and wind-dispersed species (Nybom 2004). Our results are comparable with the average expected (0.58) and observed heterozygosity (0.19) values reported when microsatellite markers were developed for M. sinensis (Hung et al 2009), although fewer samples were used in that study. Few broad scale, populationlevel microsatellite-based studies have been published on outcrossing invasive plant species; however, and only a few involve outcrossing grasses (invasive or native) (e.g.…”
Section: Discussionsupporting
confidence: 72%
“…It is interesting that despite the ability of M. sinensis to spread in the USA and form wild populations (Quinn , values for heterozygosity for the species overall were still smaller than expected for long-lived perennial species, outcrossing species, and wind-dispersed species (Nybom 2004). Our results are comparable with the average expected (0.58) and observed heterozygosity (0.19) values reported when microsatellite markers were developed for M. sinensis (Hung et al 2009), although fewer samples were used in that study. Few broad scale, populationlevel microsatellite-based studies have been published on outcrossing invasive plant species; however, and only a few involve outcrossing grasses (invasive or native) (e.g.…”
Section: Discussionsupporting
confidence: 72%
“…(). The accessions were initially screened with 85 SSRs (Table ), including 79 nuclear (Hung et al ., ; James et al ., ; Swaminathan et al ., ) and six chloroplast markers (de Cesare et al ., ). A final set of 64 nuclear and five chloroplast SSRs were used for the analyses.…”
Section: Methodsmentioning
confidence: 99%
“…sinensis germplasm accessions [19]–[20] and molecular markers, mainly random amplified polymorphic DNA (RAPD) and amplified fragment length polymorphism (AFLP) [21][23]. To date, a limited number of SSR markers have been developed for Miscanthus [24][26]. The most recent studies reported a linkage map consisting of single nucleotide polymorphism(SNP)markers in M .…”
Section: Introductionmentioning
confidence: 99%